TEORI INTEGRASI KEPEMIMPINAN, INFLUENCE TACTICS DAN KEKUASAAN DALAM MENENTUKAN ORGANISASIONAL - Diana Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2022)
Concept of leadership evolved from the traditional view of leadership (i.e. Great Man Theory) to more radical concept of leadership (i.e. transformational leadership). Research developments have accelerated the emergence of new theories about leadership. Unfortunately, academic studies that discuss about the association between leadership and power in order to achieve organizational goals are very little. This article proposes an integration model of leadership, power, influence tactics to achieve organizational outcomes.